Green Financial Management: Environmentally Friendly Financing Strategies in Manufacturing Companies - Abdul Wahab (Nomico, 2025)
The manufacturing industry plays a central role in economic growth but remains one of the largest contributors to carbon emissions, energy consumption, and environmental degradation. In response to growing sustainability pressures, this study investigates the development of a contextualized green financial management (GFM) framework for Indonesian manufacturing firms, emphasizing the integration of green financing instruments and technological innovation. A descriptive qualitative approach was employed, involving in-depth interviews with financial managers and environmental stakeholders, complemented by analysis of annual reports, sustainability disclosures, and government regulations. Data were processed through reduction, thematic categorization, and triangulation to ensure validity. The findings reveal that the adoption of green financial instruments such as green bonds, green loans, and sustainability-linked credits remains limited due to high issuance costs, regulatory uncertainty, and weak institutional support. However, firms implementing technological innovations including cleaner production technologies, renewable energy, and digital monitoring systems showed greater eligibility for green financing. Weaknesses in sustainability reporting and fragmented disclosure frameworks further hinder investor trust, while collaborative partnerships with government agencies, NGOs, and multilateral banks significantly improve access to sustainable capital. In conclusion, a GFM framework for Indonesian manufacturing firms should be built upon three pillars: accessible financing instruments, integration of technological innovation, and strengthened institutional ecosystems. This framework is expected to enhance competitiveness, attract sustainable investment, and accelerate the transition toward a low-carbon economy.